Acute Isolated Central Facial Palsy as Manifestation of Middle Cerebral Artery Ischemia. Issue 5 (8th April 2016) - Sands, Kara A.; Shahripour, Reza Bavarsad; Kumar, Gyanendra; Barlinn, Kristian; Lyerly, Michael J.; Haršány, Michal; Cure, Joel; Yakov, Yuri L.; Alexandrov, Anne W.; Alexandrov, Andrei V.
ABSTRACT: BACKGROUND: Isolated central facial palsy (I‐CFP) is attributed to a lacunar syndrome affecting the corona radiata region or pons. We examined our acute stroke registry for patients presenting with I‐CFP and localized their symptoms to a vascular lesion. SUBJECT & METHODS: Our database of consecutive patients with symptoms of acute cerebral ischemia admitted from January 2008 to December 2012 was reviewed for NIH Stroke Scale (NIHSS) scores and subcomponents. All patients with I‐CFP ± dysarthria (total NIHSS ≤ 3) had contrast‐enhanced MR‐angiography and transcranial Doppler as standard of care. All ischemic lesions were localized by MRI within 72 hours from symptom onset. RESULTS: Of 2, 202 patients with acute cerebral ischemia, 879 patients (35%) had NIHSS score ≤ 3 points (mean age 63 + 15 years, 46 % women). Nine patients (.4%) presented with I‐CFP ± dysarthria. Of these, only 1 had a lesion in the corona radiata and patent MCA, 1 had a pontine lesion without proximal vessel occlusion (2/9, or 22%). Remaining 7 patients (78%) had flow‐limiting thromboembolic mid‐to‐distal M1/proximal M2 MCA disease. Of these, 6 (86%) patients had a prominent early anterior temporal artery on MRA and nonlacunar ischemic lesions on MRI. CONCLUSIONS: Contrary to current teaching of lesion localization for an I‐CFP, our study revealed the majority of acute patients presenting with this symptom had evidence of flow‐limiting thromboembolic MCA disease rather than a lacunar lesion. Our findings underscore the essential role of comprehensive vascular imaging in patients presenting with I‐CFP, which is commonly associated with acute flow‐limiting thromboembolic MCA disease.